Redução de recaídas ao uso do álcool e aumento da ativação pré-frontal em alcoolistas submetidos à estimulação transcraniana por corrente contínua de baixa intensidade - Klauss, Jaisa (2014)
Dysfunction in frontal areas is a hallmark of alcoholism, even in alcoholic subjects with no major clinical signs of cognitive dysfunction. Studies with transcranial Direct Current Stimulation (tDCS) have been conducted in order to modulate the prefrontal cortex excitability. The aim of this study was to examine the effects of bilateral repetitive tDCS over relapses of alcohol use and over changes in the reactivity of the visual P3 (300- 500 ms) event-related potentials (ERPs) component in alcoholics. Of the 33 severe alcoholics (32 men and 01 women) treated in outpatient services, 17 were randomized to the sham-tDCS (mean age 45.5 ± 8.9 SD) and 16 (mean age 44 ± 7.8 SD) for the active tDCS group. The tDCS (2 mA , 35 cm ²) was applied bilaterally over the Dorsolateral Prefrontal Cortex (DLPFC) (cathode left / anode right) for five consecutive days, with a daily sequence of two applications of 13 minutes interposed with a 20 minutes interval (13:20:13). In the sham-tDCS group, 88.2% had relapsed to the alcohol use within 6 months. By contrast, 16 alcoholics from active tDCS group, only 50% relapsed within 6 months (Long -rank test: p = 0.02). Also, the perception of quality of life of the active tDCS group improved (p = 0.02) and there was an increase in scores on the environmental domain (p = 0.04). Moreover, in the sham-tDCS group, the DLPFC activity was significantly (p < 0.0001, non-parametric Wilcoxon test) decreased after treatment especially under alcohol-related cue presentation, whereas the activity of DLPFC was significantly increased (p < 0.0001, Wilcoxon nonparametric test) in the tDCS group under both, neutral and alcohol-related cues. These changes were significantly different between groups (p < 0.0001, ANCOVA). These results demonstrated that bilateral tDCS over the DLPFC significantly reduced relapses to the alcohol use and improved perception of quality of life, and significantly increased the activation of prefrontal area in severe alcoholics.